The Dominant Personality Type In Gastroesophageal Reflux Disease (GERD) Patients At Dr. Soetomo General Hospital Surabaya - Viorelina, Angela Romauli; Abdurachman; Ulfa Kholili; Izzatul Fithriyah; Delwi Novita; Anita Zara Weinheimer (Faculty of Medicine, Universitas Airlangga, 2026)
Introduction: Gastroesophageal Reflux Disease (GERD) is a disorder of reflux of gastric contents into the esophagus, which can cause symptoms and complications. The global prevalence of GERD is 25% in adults, 20% in Western countries, and 3–5% in Asia, and it continues to increase. Physical therapy has been widely used, ranging from diet, exercise, and medication to surgery. Meanwhile, non-physical therapy, such as personality changes, has not been developed much. The Big Five Personality is a personality theory that consists of five dimensions, namely openness, conscientiousness, extraversion, agreeableness, and neuroticism, with each dimension representing different aspects of personality and related to health. This research aims to identify the dominant personality traits of GERD patients based on the Big Five personality model. Methods: This research used secondary data from medical records of GERD patients at RS Dr. Soetomo Surabaya and primary data from the Big Five Personality questionnaire interview using the descriptive cross-sectional method. Results: A total of 51 GERD patients at Dr. Soetomo Surabaya; it was found that the mean age of patients was 34.23 (SD 9.526) years, and there were 26 female patients (51%) and 25 male patients (49%). The interview results revealed that agreeableness was the dominant personality type. Conclusion: According to the Big Five Personality Theory, the dominant personality type in GERD patients at Dr. Soetomo General Hospital Surabaya is agreeableness.